Antibacterial properties of Solenostemma argel (Del.) Hayne against Salmonella strains from chicken meat: integrated GC–MS phytochemical profiling and molecular docking analysis - Alhudhaibi, Abdulrahman Mohammed; Dahab, Mahmoud; Idriss, Hajo; Almoteri, Megren Faisal; Abdallah, Emad M. (Frontiers in Nutrition, 2025)
BackgroundSalmonella enterica is a leading cause of foodborne illness worldwide and poultry products, particularly chicken meat and there is growing interest in using plant extracts to protect chicken meat from Salmonella contamination during refrigeration. Solenostemma argel is a medicinal plant traditionally used to treat gastrointestinal disorders and quantitative data on its activity against Salmonella enterica are limited.MethodsMethanolic leaf extract was profiled by GC–MS to document major phytochemical classes. Antibacterial activity against clinical/retail S. enterica isolates was evaluated by disc diffusion and broth microdilution to determine inhibition zones, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). A panel of GC–MS–identified constituents was subjected to in silico computational study based on oral-toxicity prediction and molecular docking against modelled outer-membrane proteins implicated in LPS assembly and membrane integrity (OmpV, LptE) to prioritize plausible membrane-active leads.ResultsThe methanolic extract displayed modest inhibition in disc-diffusion assays (mean inhibition zones were 7.8–9.7 mm). All S. enterica isolates shared a uniform MIC of 12.5 mg/ml; MBCs were strain-dependent (25 mg/ml for one isolate, 100 mg/ml for two isolates), yielding MBC/MIC ratios of 2–8 and indicating primarily bacteriostatic activity for some strains. GC–MS profiling revealed several volatile and semi-volatile metabolites of potential biological interest. However, it is important to note that some peaks, such as 1,3-dioxane and 2-[2-[2-(2-acetyloxyethoxy)ethoxy]ethoxy]ethanol, may represent laboratory-derived contaminants rather than genuine plant metabolites, emphasizing the need for rigorous contamination controls and complementary analytical approaches in future work. In silico docking prioritized a steroidal candidate [Estra-1,3,5(10)-trien-17β-ol] with the highest predicted affinities to OmpV (−7.9 kcal·mol−1) and LptE (−6.7 kcal·mol−1). Toxicity predictions suggested low oral toxicity for the majority of screened constituents.ConclusionThe methanolic leaf extract of Solenostemma argel exhibited moderate to weak in vitro anti-Salmonella activity, supported by computational docking results, and provide a foundation for further isolation, purification, and characterization of its active constituents.